Kinetics of cooking of unsoaked and presoaked split peas (Cajanus cajan). Issue 5 (6th February 2017) - Shinde, Yogesh H.; Amogha, V.; Pandit, Aniruddha B.; Joshi, Jyeshtharaj B.
Abstract: Cooking methods used currently are about 10–15% thermally efficient. To develop better efficient methods of cooking, it is desirable to understand the kinetics of cooking. Experiments were performed with both unsoaked and presoaked split‐peas (commonly known as Dhal in India) at three different temperatures (90 °C, 94 °C, and 98 °C). It has been found that Dhal does not cook at 90 °C even after 120 min of cooking time. Pre‐soaking of Dhal does not found to reduce the time required for cooking. In the present work, the rate of water absorption and hardness of cooked Dhal grains were measured. Both the measurements were used for the estimation of cooking kinetics. The rate constants for cooking of unsoaked and presoaked Dhal were found to be ∼ 4 × 10 −4 s −1 at 94 °C and ∼8 × 10 −4 s −1 at 98 °C. Regime of operation for cooking of Dhal is found to be diffusion controlled based on swelling particle model of (Singhal et al., 2012). Practical applications: About 40 % of the total energy consumed in the developing World (population more than 4 billion) is used for cooking. In developing countries, where 70 % of the population resides in rural areas, open pan cooking method (efficiency ∼15%) is still the most widely used. Pressure cooker development has improved the thermal efficiency to some extent. There is an urgent need to employ an energy efficient engineering solution for preparing hygienic, nutritious meals, which also has advantages of energy efficiency, ease of operation and efficient resource utilization. In order to design any efficient cooking device, kinetics of cooking for particular food material must be studied. Shinde et al., (2016), Joshi et al., (2012) have designed the energy efficient batch and continuous cookers. Presented work utilizes simple method for determining kinetics of spilt peas, which can be easily extended to obtain kinetics of any other food material.